PARTISIPASI ISTRI NELAYAN PADA ORGANISASI FORMAL - Casmiwati, Dewi (Jurnal Ilmu Administrasi Negara, 2014)
InKedung Cowek, Bulak, Surabaya City, the fisheries’s wives have low participation informal organization. This is an irony because besides they are majority in population,also the function of those institutions are to bring the better life condition of society,it’s hard to achieve if the society arround them is not involved. This research wants toanswer the question: what factors that influence the rate participation of fisheries’swives in formal organization.The research uses descriptive qualitative methods withindepth interview, observation and documentation in collecting both of primary andsecondary data. The research result shows that the factors that influence the fisheries’wives in formal organization are limited education and skill of them. Beside that,limited skill only on fisheries make them enable to work in fisheries sector, not others.This condition is worst by the local culture that positioned them in domestic affairsthan outside and the double roles as wives as well as workers and it’s difficult for themto participate at public sector. Keywords: participation, formal organization, double roles, domain public, domaindomestic